2
$\begingroup$

Ok so I know the answer of $\frac{d}{dx}x\sin(x) = \sin(x)+ x\cos(x)$...but how exactly do you get there? I know $\frac{d}{dx} \sin{x} = \cos{x}$. But where does the additional $\sin(x)$ (in the answer) come in?

$\endgroup$
  • 3
    $\begingroup$ What's the product rule for the derivative? $\endgroup$ – Daniel Fischer Jul 14 '13 at 17:26
  • $\begingroup$ en.wikipedia.org/wiki/Product_rule $\endgroup$ – lab bhattacharjee Jul 14 '13 at 17:28
  • 1
    $\begingroup$ Wolframalpha.com with "show steps" option will write out a derivation for this and many other routine problems. $\endgroup$ – zyx Jul 14 '13 at 18:03
11
$\begingroup$

A bit of intuition about the product rule:

Suppose that you have a rectangle whose height at time $t$ is $h(t)$ and whose width at time $t$ is $w(t)$. Then the area at time $t$ is $A(t)=h(t)w(t)$. Now, as the time changes, how does the area change?

Rectangle image

(Please, forgive my use of paint here.)

Say the white rectangle was from time $t$, and the larger rectangle at time $t+\Delta t$. We gain three new regions of area: the green one, the blue one, and the gray one.

The green area is $\Delta h\cdot w(t)$, where $\Delta h$ is the change in height from time $t$ to time $t+\Delta t$; the blue area is, similarly, $\Delta w\cdot h(t)$, and the gray area is $\Delta h\cdot\Delta w$. So, we have $$ \Delta A=\Delta h\cdot w(t)+\Delta w\cdot h(t)+\Delta h\cdot\Delta w. $$ Now, when $\Delta t$ is really small, we expect $\Delta h$ and $\Delta w$ to be really small as well; so, their product is tiny. Hence $$ \Delta A\approx \Delta h\cdot w(t)+\Delta w\cdot h(t), $$ or $$ \frac{\Delta A}{\Delta t}\approx\frac{\Delta h}{\Delta t}\cdot w(t)+\frac{\Delta w}{\Delta t}\cdot h(t). $$ Does this look at all like the product rule? Letting $\Delta t\rightarrow0$, this approximation (properly formalized, of course) leads us to the formula $$ \frac{d}{dt}\left[w(t)\cdot h(t)\right]=\frac{dA}{dt}=\frac{dh}{dt}\cdot w(t)+\frac{dw}{dt}\cdot h(t) $$

$\endgroup$
7
$\begingroup$

Hint: Use the product rule for derivatives.

Alternately, proceed by definition, using trig properties (continuity, angle sum):

$$\begin{align}\frac{d}{dx}[x\sin x] &= \lim_{h\to 0}\frac{(x+h)\sin(x+h)-x\sin x}h\\ &= \lim_{h\to 0}\frac{h\sin(x+h)}h+x\lim_{h\to 0}\frac{\sin(x+h)-\sin x}h\\ &= \lim_{h\to 0}\sin(x+h)+x\lim_{h\to 0}\frac{\sin x\cos h+\sin h\cos x-\sin x}h\\ &= \sin x+x\cos x\lim_{h\to 0}\frac{\sin h}h+x\sin x\lim_{h\to 0}\frac{\cos h-1}h.\end{align}$$ It then remains to show that $\lim\limits_{h\to 0}\frac{\sin h}h=1$ and $\lim\limits_{h\to 0}\frac{\cos h-1}h=0,$ either as "special limits" or by some other means.

$\endgroup$
  • $\begingroup$ explanation please? $\endgroup$ – madman75 Jul 14 '13 at 17:27
  • $\begingroup$ Check out the link. Have you seen that rule before? $\endgroup$ – Cameron Buie Jul 14 '13 at 17:29
  • $\begingroup$ oh ok...i think i see. i use f'(x) = f(x)*d/dx g(x) + g(x)*d/dx f(x)? $\endgroup$ – madman75 Jul 14 '13 at 17:35
  • $\begingroup$ Exactly. There are other ways to go, too. (Updating my answer now with one alternative.) $\endgroup$ – Cameron Buie Jul 14 '13 at 17:41
  • 1
    $\begingroup$ By the way $\frac{\cos h-1}{h}=\frac{(\cos h-1)(\cos h+1)}{h(\cos h+1)}=\frac{-\sin^2 h}{h(\cos h+1)}=\frac{-\sin h}{h}\frac{\sin h}{\cos h+1}\to 0$ as $h\to 0$. So this limit folows from $\lim_{h\to 0}\frac{\sin h}{h}$. $\endgroup$ – Baby Dragon Jul 14 '13 at 19:43
3
$\begingroup$

Depending on how familiar you are with the chain rule and derivative of logarithmic functions, you could differentiate $x \sin{x}$ using this alternate method that doesn't directly use the product rule,

$$\begin{align} y &= x \sin{x} \\ \ln(y) &= \ln( x \sin{x}) \\ \ln(y) &= \ln(x) + \ln(\sin{x}) \\ \frac{1}{y} \frac{dy}{dx} &= \frac{1}{x} + \frac{\cos{x}}{\sin{x}} \\ \frac{dy}{dx} &= \left( \frac{1}{x} + \frac{\cos{x}}{\sin{x}} \right) \cdot y \\ \frac{dy}{dx} &= \left( \frac{1}{x} + \frac{\cos{x}}{\sin{x}} \right) \cdot x \sin{x}\\ \frac{dy}{dx} &= \sin{x} + x \cos{x}. \\ \end{align}$$

$\endgroup$
1
$\begingroup$

You are probably expected to do this by the product rule, which says:

$(v \cdot w)'=vw'+v'w$

Setting $v=x$ and $w=\sin x$ (it doesn't matter which is which)

$v'=1$ and $w'=\cos x$ . Substituting into the formula:

$(v \cdot w)'=x \cos x+(1) \cdot \sin x$

$x \cos x+ \sin x$

which is your answer.

$\endgroup$
1
$\begingroup$

$x\sin(x)$ is the product of two functions. It's easier to see that there are two functions here if you rewrite components of the problem as $f(x)=x$ and $g(x)=\sin(x)$. If the two functions $f(x)$ and $g(x)$ are differentiable (the derivative exists), then their product is also differentiable.

Now apply the product rule: ${(fg)}' = {f}'g+f{g}'$ to get $x\cos(x)+\sin(x)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.